1998
DOI: 10.1152/physiologyonline.1998.13.4.170
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Mystery of Goldblatt Hypertension

Abstract: In hypertension caused by unilateral renal artery stenosis, the nonstenotic kidney becomes renin depleted but fails to prevent hypertension. The nonstenotic kidney mysteriously develops elevated intrarenal angiotensin II (ANG II) content. Rats chronically infused with ANG II exhibit a similar hypertensive process. The augmentation of intrarenal ANG II is due to receptor-mediated internalization and continued ANG II formation, which provide a hypertensinogenic stimulus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
129
0
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(142 citation statements)
references
References 12 publications
10
129
0
3
Order By: Relevance
“…In the early stage of renovascular hypertension, renin secretion from the non-clipped kidney is reduced by the elevated perfusion pressure. 15 In contrast, the elevated pressure inhibits the processing of prorenin to renin, leading to accumulation of prorenin in renal juxtaglomerular cells, 16 and the tissue Ang II levels of the nonclipped kidneys rise gradually during the late stage of renovascular hypertension, 17 probably because of a prorenin-dependent mechanism. In the present study, activated prorenin and tissue Ang II levels were upregulated without any changes in (P)RR mRNA expression in the non-clipped kidneys.…”
Section: Long-term Effects Of Hrp On 2k1c Kidneys M Ryuzaki Et Almentioning
confidence: 99%
“…In the early stage of renovascular hypertension, renin secretion from the non-clipped kidney is reduced by the elevated perfusion pressure. 15 In contrast, the elevated pressure inhibits the processing of prorenin to renin, leading to accumulation of prorenin in renal juxtaglomerular cells, 16 and the tissue Ang II levels of the nonclipped kidneys rise gradually during the late stage of renovascular hypertension, 17 probably because of a prorenin-dependent mechanism. In the present study, activated prorenin and tissue Ang II levels were upregulated without any changes in (P)RR mRNA expression in the non-clipped kidneys.…”
Section: Long-term Effects Of Hrp On 2k1c Kidneys M Ryuzaki Et Almentioning
confidence: 99%
“…1 Previous studies have shown that activation of angiotensin II (ANG II) type 1 (AT 1 ) receptors predominantly mediates the effect of ANG II on the renal vasculature and is largely responsible for the development of hypertension in ANG II-dependent models of hypertension. [2][3][4] However, two subtypes for AT 1 receptors have been identified in mouse and rat (AT 1A and AT 1B ). 5 It has been demonstrated that the AT 1A receptors are the predominant subtype in most tissues, with the exception of the adrenal cortex, pituitary gland, and glomerulus, where the AT 1B receptors are also highly expressed.…”
mentioning
confidence: 99%
“…The 2K1C hypertensive rat is a renovascular hypertensive model, which is characterized by elevated Ang II expression caused by ischemia in clipped kidney and shear stress in nonclipped kidney. The activity of RAS plays a key role in the development and maintenance of high BP through the production of Ang II [34,35] . Ang II has a high affinity for AT 1 receptors, which are responsible for Ang II-induced hypertension.…”
Section: Discussionmentioning
confidence: 99%